Dealing with climate change on small islands: Toward effective and sustainable adaptation - Klöck, Carola (Universitätsverlag Göttingen, 2019)
Small islands have received growing attention in the context of climate change. Rising sea-levels, intensifying storms, changing rainfall patterns and increasing temperatures force islanders to deal with and adapt to a changing climate. How do they respond to the challenge? What works, what doesn't - and why? The present volume addresses these questions by exploring adaptation experiences in small islands across the world's oceans from various perspectives and disciplines, including geography, anthropology, political science, psychology, and philosophy. The contributions to the volume focus on political and financial difficulties of climate change governance; highlight the importance of cultural values, local knowledge and perceptions in and for adaptation; and question to what extent mobility and migration constitute sustainable adaptation. Overall, the contributions highlight the diversity of island contexts, but also their specific challenges; they present valuable lessons for both adaptation success and failure, and emphasise island resilience and agency in the face of climate change.